(untitled) (Journal of Adat Recht, 2025)
Local wisdom in customary law plays a crucial role in maintaining environmental sustainability, particularly in indigenous communities that still uphold traditional values. However, this role has not been fully recognized and integrated into the national environmental legal system. This study aims to analyze how customary law functions as an environmental protection instrument and propose strategies for its integration within the national legal framework. The approach used is descriptive qualitative with a juridical-sociological research method, conducted through case studies in three indigenous communities: the Baduy (Banten), Dayak Kenyah (North Kalimantan), and Subak Bali. Data collection techniques included interviews, observation, and documentation studies, which were then analyzed thematically. The results show that customary legal practices such as Leuweung Kolot, Tane’ Olen, and the Subak system have proven effective in maintaining environmental sustainability through customary norms, social sanctions, and spiritual values. However, formal recognition of customary territories remains limited. In conclusion, customary law has great potential as a legitimate and sustainable environmental protection instrument, and therefore needs to be substantively integrated into national environmental policy through a collaborative and community-based approach.